PENGARUH PERTUMBUHAN EKONOMI, PENDIDIKAN DAN ANGKATAN KERJA TERHADAP TINGKAT PENGANGGURAN DI PROVINSI RIAU - Hesmawati, Hesmawati; Susanti, Septria (Jurnal Ekonomi Sakti, 2024)
It is widely believed that the workforce, education, and economic growth have a significant impact on the unemployment rate. The aim of this research is to determine the relationship between economic growth, employment, unemployment. This research methodology is quantitative research using descriptive techniques. This research uses secondary data, specifically annual statistics regarding the impact of economic growth, education and labor force participation, on the unemployment rate in Riau Province. Next, it was processed using SPSS Version 21 research software used in this research and the Multiple Linear Regression analysis tool. Research findings show that the workforce, economic growth and education have a major influence on the unemployment rate in Riau Province. With a Sig of 0.028 < α 0.05, the Economic Growth variable has an influence on the Unemployment Rate. In relation to Education (X2) there is a significant influence of 0.004 < α 0.05 on the Unemployment Rate (Y). Furthermore, there is no significant influence of Sig.0.52 > α 0.05 from the Labor Force (X3) on the Unemployment Rate (Y). Simultaneously, the independent variables of this research have a significant effect on the unemployment rate in Riau Province during 1993–2023 with a value of (Sig. 0.005 < α 0.05). With a coefficient of determination value of 0.378, it can be concluded that the labor force (X3), education (X2), and unemployment rate (Y) in Riau Province each contribute 37.8% of the total and other factors contribute the remaining 62.2% . These findings can be a valuable reference for the government in its efforts to reduce unemployment and improve community welfare by conducting comprehensive and methodological research.Keywords: Economic Growth, Education, Labor Force, Unemployment